Oscillatory activity, phase differences, and phase resetting in the inferior olivary nucleus - Lefler, Yaara; Torben-Nielsen, Benjamin; Yarom, Yosef (Frontiers in Systems Neuroscience, 2013)
The generation of temporal patterns is one of the most fascinating functions of the brain. Unlike the response to external stimuli, temporal patterns are generated within the system and recalled for a specific use. To generate temporal patterns one needs a timing machine, a 'master clock' that determines the temporal framework within which temporal patterns can be generated and implemented. Here we present the concept that in this putative 'master clock', phase and frequency interact to generate temporal patterns. We define the requirements for a neuronal ‘master clock’ to be both reliable and versatile. We introduce this concept within the inferior olive nucleus, which, at least by some scientists, is regarded as the source of timing for cerebellar function. We review the basic properties of the subthreshold oscillation recorded from olivary neurons, analyze the phase relationships between neurons, and demonstrate that the phase and onset of oscillation is tightly controlled by synaptic input. These properties endowed the olivary nucleus with the ability to act as a 'master clock'.